AB0501 Adverse events with treatment regimens of rheumatoid arthritis (RA) reported by patients applying smart system of disease management (SSDM) mobiles tools: a cohort study of ra patients in china. (12th June 2018) - Wang, Y.; Yang, J.; Wei, H.; Li, C.; Mu, R.; Wu, B.; Wang, H.; Wang, Y.; Wang, X.; Guo, H.; Xue, J.; Ru, J.; et al.
Abstract : Background: Hepatic, hematologic and other adverse events (AE) during treatment in RA patients are unavoidable. And monitoring AE in long-term treatment is quite necessary as a part of chronic disease management. SSDM is a smart mobile tool to help patients upload their therapeutic regimens, lab test records and report AEs. Our previous study showed that patients in China can master the application of SSDM after training. Objectives: To determine and compare the incidence of adverse events during treatment of RA with different therapeutic regimens, focusing on mono and combination therapy. Methods: The SSDM includes interfaces of both physicians' and patients' application. Patients were educated to enter the data of lab test records and treatment regiments once a month, all data can be synchronised automatically to the authorised physicians' mobile tool, which formed a large patient reported database. The rheumatologists can also adjust treatment regiments base on patients' profile. Results: From Aug 2014 to Jan 2018, a total of 7048 RA patients from 480 centres in China were entered in the cohort study. These patients contributed more than 12 600 patient-years (PY) of total followup. The mean age was 48.98±16.08 (18 to 99) years and the median disease duration was 23.27 months. The treatment regimens include mono or combination of leflunomide(LEF), MTX, hydroxycholoqine (HCQ), sulfasalazine(SSZ), glucocorticoid(GC), biologic DMARD, Tripterygium wilfordii, meloxicam, celecoxib, iguratimod, etc. In this database the five most common treatment regimens is LEF monotherapy (3801 PY), MTX monotherapy (1321 PY), LEF +MTX (1086 PY), HCQ monotherapy (715 PY), LEF +HCQ (576 PY). The incidence rate of hepatic events was lower for LEF monotherapy (35 events/1000 PY) than MTX (52 events/1000 PY) and LEF +MTX combination therapy (115 events/1000 PY) (p<0.01). The incidence rate of leukopenia was lower for LEF monotherapy (42 events/1000 PY) and MTX monotherapy (39 events/1000 PY) than LEF +MTX combination therapy (84 events/1000 PY) (p<0.01). Conclusions: The findings show that mono or combination of csDMARDs are the most commonly used drugs in Chinese RA patients. And AEs may be well described in this patient report database because of the large sample sizes and empowering patient themselves. RA patients can get better safety in the long-term treatment via SSDM. Disclosure of Interest: None declared